Methods For Construction Of The Zhegalkin Polynomial - Umarov, Khabibullo Rakhmatullayevich (TLEP – International Journal of Multidiscipline, 2025)
It is known that any Boolean function can be represented by a Zhegalkin polynomial (a polynomial modulo two), and this representation is unique up to a permutation of terms. Some of the most well-known methods for constructing such a polynomial have been given.